STRATEGI BRANDING PUBLIC RELATIONS PERUSAHAAN ADI TV DI ERA DIGITAL - Yohanes Meilino Petra Giyatno (Bajang Institute, 2024)
A branding strategy is a plan designed to build and maintain a strong and positive brand image in the minds of consumers. Branding strategies are important because they are used by companies to ensure that their products or services are recognized, valued, and remembered by the target market. This research aims to analyze the branding public relations strategy at ADI TV company in the digital era. This research is a qualitative descriptive research. The research subject is public relations. The data collection techniques used are interviews, observation and documentation. The data validity used is source triangulation. Data analysis is done through data collection, data reduction, data presentation and conclusion drawing. The results showed that there are strategies carried out by public relations in branding in the digital era. Attracting, encouraging, and influencing strategies are strategies carried out by public relations at ADI TV companies in branding. The three strategies show effective results in branding ADI TV in the digital era.